Hydro-Oceanographic Characteristics In Karimunjawa Coastal Waters During The 1st Transitional Season - Yulius Yulius; Joko Prihantono; Dino Gunawan; Muhammad Ramdhan; August Daulat; Nur Kholik Kurniana Putra (Jurnal Segara, 2021)
This study aims to determine oceanographic characteristics such as tides, waves, and currents in Karimunjawa Coastal Waters during the 1st transitional season and to update the oceanographic database for spatial management evaluation in the region. The tidal characteristics were obtained from the least square method analysis using World Tide software based on Matlab programming language, while wave and current characteristics obtained from 2-dimensional numerical modeling using Mike 21 software on the flow model and spectral wave module. The primary data used were the significant wave height (Hs), wave peak period (Tp), and ocean current components (u and v velocity) on 13-26 May 2016 using the Sontex Argonaut XR type Acoustic Doppler Current Profiler (ADCP) equipment. Tide data were predicted for the Kemujan Islands station from 1-31 March 2020. Secondary data for additional numerical model input were obtained from ERA5-reanalysis in the form of Hs, Tp, u, and v wind velocity data for May 2020 with a temporal resolution of 20 minutes, while bathymetry data derived from GEBCO Satellite Derivated Bathymetry (SDB) data. The tide analysis results showed that Karimunjawa waters are a single daily mixed tidal type. The wave characteristic moves from east to west with high waves reached 0.9 meters and a peak period of 7 seconds. The eastern side of Karimunjawa Island, Kemujan Island, and the western area have a calmer wave. The current characteristic moves northeastward with a speed of 5-28 cm/s, which concludes that in several locations, such as the Menjangan Besar-Menjangan Kecil strait, the currents depend on the tidal conditions.